Primary lung sebaceous carcinoma successfully treated with radiotherapy and pembrolizumab: A case report. Issue 3 (9th December 2022) - Jodai, Yasumiko; Hamada, Shohei; Yamada, Mikiko; Masuda, Yuiko; Anai, Moriyasu; Jodai, Takayuki; Tomita, Yusuke; Saeki, Sho; Ichiyasu, Hidenori; Sakagami, Takuro
Abstract: Sebaceous carcinoma is a rare cutaneous malignant tumor, usually occurring on the eyelids, head, neck, and trunk. There have been few reports about sebaceous carcinoma with primary lung cancer, for which optimal therapy has not yet been established. A 70‐year‐old man presented with a mass in the left iliac bone and tumor of the lower left lung. The morphological characteristics of the iliac bone biopsy pathology and immunostaining results showed sebaceous gland differentiation. After systemic examination, we diagnosed a primary lung sebaceous carcinoma with intrapulmonary and bone metastases. PD‐L1 was positive in 1%–24% of tumor cells, and microsatellites were stable. We detected protein kinase B (AKT1) mutations using the Oncomine Dx target test. Palliative radiotherapy (RT) of a total of 45 Gy was provided in 15 fractions to the left iliac region, which resulted in a 25% reduction in the tumor size. Subsequently, four courses of first‐line pembrolizumab led to a 30% reduction in the total tumor count. RT and pembrolizumab may be treatment options for certain rare primary sebaceous carcinomas of the lungs. A synergistic effect from RT and subsequent administration of immune checkpoint inhibitors may have contributed to tumor reduction. Abstract : Primary sebaceous carcinoma of the lung is very rare, and no effective treatment has been yet established. We successfully treated lung sebaceous carcinoma with sequential treatment with radiotherapy and anti‐PD‐1 antibody therapy. The tumor had AKT1 mutation and was positive for PD‐L1 expression, suggesting AKT‐PD‐L1 pathway may be implicated in the response to therapy.